The Freedom to Use Social Media in Children from the Contemporary Ulema Perspective: A Case Study in Barru Regency, South Sulawesi - Zulhas'ari Mustafa; Rikawati Rikawati (PAREWA SARAQ: JOURNAL OF ISLAMIC LAW AND FATWA REVIEW, 2022)
This study’s main problem was the perspective of contemporary fiqh scholars on the freedom to use social media in children. A qualitative method was adopted using a normative sociological approach, and data were collected through observation, interviews, and documentation. Furthermore, the interviewees consist of children and their parents in Tanete Riaja District, Barru Regency. The results showed that children in Tanete Riaja District, Barru Regency had many positive impacts when viewed from the perspective of contemporary fiqh scholars, including assisting in obtaining information for learning and doing group assignments. There were also negative impacts, such as children’s addiction to social media, eye health problems, and others. As an implication of this study, it is hoped that children can be wiser in using social media. Additionally, parents can supervise their children properly when using social media.